Identification, characterisation and phylogenetic analysis of commensal bacteria isolated from human breast milk in Malaysia - Hassan, Zubaida; Mustafa, Shuhaimi; Abdul Rahim, Raha; Mat Isa, Nurulfiza (Universiti Putra Malaysia Press, 2016)
Human breast milk microbiota is essential for infant immune system development, maturation and protection against infection. However, there is scarce information on the fluid’s microbiological composition from Malaysia. The objective of the study was to isolate, identify and characterise commensal bacterial population present in human breast milk from Malaysia. One hundred bacteria were isolated from the human breast milk of healthy lactating women (n=30). After preliminary screening, 20 isolates were characterised using both phenotypic and molecular techniques. The results indicated that most frequently identified bacteria in this study were E. faecalis and S. hominis. These organisms alongside E. cloacae were all metabolised D-Maltose, Sucrose, D-Turanose, α-D-Glucose, D-Fructose, D-Mannose, D-Galactose, D-sorbitol and D-Mannitol and were able to grow at pH 5 and 6, 1% sodium lactate, 1%, 2% and 8% NaCl. BLAST showed over 99% similarity to those deposited in Genbank. Phylogenetic-relatedness was depicted using neighbour-joining method and had two clades with 100% bootstrap. These findings provided insight into the nature, characteristics and also phylogenetic-relatedness of bacteria present in human milk from Malaysia. Isolation and identification of commensal bacteria from human milk are considered the first step for future studies on the benefit of these organisms towards human health.